ANALISIS KINERJA PEGAWAI YANG DIPENGARUHI KOMUNIKASI, PELATIHAN KERJA DAN BUDAYA ORGANISASI MELALUI KEPUASAN KERJA SEBAGAI INTERVENING PADA LEMBAGA PEMBINAAN KHUSUS ANAK LOMBOK TENGAH - Bobby Lintang A; Yohanes Joni P; Kurnia Endah R (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to analyze employee performance which is influenced by communication, job training, and organizational culture through job satisfaction as an intervening. Quantitative research method with explanatory research approach. The sampling technique using the saturated sample method was for all LPKA Lombok Tengah employees who had civil servant status, totaling 83 people. Data analysis used the SEM-PLS method, results showed that 82.5% variation in performance can be explained from communication, job training, organizational culture and job satisfaction and 77.7% variation in job satisfaction can be explained through communication, job training and organizational culture. Through direct effect analysis on path coefficient organizational culture is the factor that most influences job satisfaction, while job training is the factor that most influences performance. By testing the hypothesis, it can be seen that all variable relationships, both direct and indirect effects, produce positive and significant values, only the direct relationship of organizational culture to performance produces positive and insignificant values. However, in the indirect effect relationship of communication culture on performance through job satisfaction the results of the hypothesis produce positive and significant results. So it can be concluded that the mediating role of job satisfaction in the relationship of communication and job training to performance as a partial mediation effect, while the relationship of organizational culture to performance as a full mediation (full mediation) is 0.101.